Yearbook of Chinese Theology 2019 - Huang, Paulos Z., (Yearbook of Chinese Theology ;, 2019)
The Yearbook of Chinese Theology is an international, ecumenical and fully peer-reviewed annual that covers Chinese Christianity in the areas of Biblical Studies, Church History, Systematic Theology, Practical Theology, and Comparative Religions. It offers genuine Chinese theological research previously unavailable in English, by top scholars in the study of Christianity in China. The 2019 volume highlights the five-disciplines of Karl Barth and Sino-Christian theology and its guest editor is Thomas Xutong Qu. Further contributions are from: Paulos Huang and Thomas Xutong Qu, Wai Luen Kwok, Xin Leng, Shi-Min Lu, Quan Li, G. Wright Doyle, Jin Li and Li Ma, Liang Hong, Liang Hong, Shao Kai Tseng, Xiangchen Sun.